MOTIVATION TOWARD ENGLISH LANGUAGE PERFORMANCE OF A NON-ENGLISH MAJOR STUDENT - Sinap, Florentina; Susilawati, Endang; Rosnija, Eni (FKIP - Universitas Tanjungpura, 2021)
The purpose of this research was to identify what kind of motivations (instrumental or integrative) had been affected the student’s English language performance at college. This research design was a case study and the participant was a student of Law Faculty of Tanjungpura University. The data were obtained from supported documents such as the student’s paper grade, certifications of participation, and interview results. The data analysis is focused on modifying the Gardner socio-educational model called Attitude, Motivation Test Battery (AMTB) in Masgoret and Gardner’s conducted study (2003). It covers the aspects of attitudes toward the learning process, motivation, integrative orientations, and instrumental orientations. The results of this research were classified into two points. The first finding showed that the student had been motivated instrumentally and integratively, and the second finding showed that the student had mostly been motivated instrumentally. For integrative aspects, being integrated with the society of the target language is not considered to be prioritized. The student expects it while doing his long-term practical goals, and meanwhile, for instrumental aspects, they cover academic goals, career goals, and self-development. Overall, it can be simplified that motivations had been contributed to the student’s achievements by determining his persistence in reaching a specific goal.